Sistem Online Recruitment Berbasis Web Pada Pt.xyz Menggunakan Metode Simple Additive Weighting (saw) - Maidel Fani; Ika Anggun Lestari (Politeknik Caltex Riau, 2021)
XYZ is a manufacturing company located in the city of Batam. most of the activities of employees at PT XYZ Batam are still carried out offline like new employees, where HRD still checks every application sent by candidates via email for staff and post office for non-staff. The impact on PT. XYZ is if you are still using the current manual system, all job applications that will not be used will pile up. Meanwhile, email messages that are received in large numbers will cause spam and take a long time to choose, therefore the author will create and design online recruitment based on an information web system using the Decision Support System (DSS) method that can help HRD in the recruitment process The Decision Support System used by the author is the Simple Additive Weighting method, also known as summation. This method automatically selects prospective employees who have submitted applications through a system that matches their work experience, study program, and skills. Thus, Simple Additive Weighting is the most appropriate method for decision making in employee recruitment